Reimbursement by current German Diagnosis-Related Groups system penalises complex congenital heart surgery. (13th May 2013) - Sinzobahamvya, Nicodème; Kopp, Thorsten; Arenz, Claudia; Blaschczok, Hedwig C.; Hraska, Viktor; Asfour, Boulos
Abstract: A total of 458 hospital stays during the year 2011 were analysed to determine whether reimbursement by the current German Diagnosis-Related Groups system covers the costs incurred during hospital stay for congenital heart surgery. The costs of every hospital stay were estimated according to the guidelines of the Institute for the Hospital Remuneration System, an institute responsible for encoding hospital reimbursement in Germany. Cost-weight values of the year 2012 were applied for reimbursement. Related additional compensations were also included. Hospital costs ranged from 8896.26 to 193, 671.94 euros per case, with a mean of 30, 597 and standard deviation of 25, 032 euros. Reimbursement varied from 8630.35 to 173, 710.65 euros, with a mean of 25, 514 and standard deviation of 18, 497 euros: an underfunding of 17%. Fifty-nine per cent (271/458) of cases were classified, according to Aristotle complexity score, in higher comprehensive complexity: Levels 4–6. Costs highly correlated with complexity levels (Spearman's r coefficient = 0.89) and the regression was linear. Underfunding increased, linearly, from 6% for procedures with Level 1, lowest comprehensive complexity, to 23% for those with Level 6, highest complexity. In conclusion, this study demonstrates that reimbursement by the current German Diagnosis-Related Groups system increasingly penalises complex congenital heart surgery. Aristotle complexity score could help to correct this prejudicial situation.